Development of pulp moulded packaging samples from empty fruit bunch fibre - Qiuyun, Liu; Ceri, Loxton; Mohamed, Amir Alzahari; Jawaid, Mohammad; Radek, Braganca; Robert, Elias (Universiti Putra Malaysia Press, 2021)
Single-use plastic packaging is a cause of rising environmental concerns due to high production volumes, short usage time, and problems related to end of life management and release into the environment. As a result, there is an increased demand to develop alternative non-plastic packaging from agricultural waste materials. This paper reported findings for converting, via atmospheric refining, waste oil palm empty fruit bunch (EFB) fibres into a fibrous pulp which can then be used to produce three-dimensional pulp moulded products. By optimising the mould design, the efficiency of vacuum suction was improved, which in turn helped to improve fibre distribution and the quality of moulded trays; such moulded trays are suitable for the containment of food items such as fruit and vegetables. Furthermore, when combined with compostable barrier treatments, lidding and adhesive films currently under development, there is an opportunity to provide a complete biocompostable packaging solution for some food items. Furthermore, as these pulp moulded packaging products are made from agricultural fibre wastes rather than plastics, the pulp moulded trays are recyclable or compostable at the end of life. Therefore, if a release does occur into the environment, it would not persist.